Tari Eklek Sebagai Dasar Pembentukan Kepenarian di Lembaga Kursus dan Pelatihan Pradapa Loka Bhakti - Wirastuti Susilaningtyas; R. M. Pramutomo (Departement of Mathematics Education, 2023)
Eklek dance is a type of dance performance created by the innovations of Sukarman, who was inspired by the cultural phoenomena within the community of the village Pelem, in the district of Pringkuku, in the regency of Pacitan. The existence of this dance is supported by public interest in entertainment, and also serves as a form of cultural preservation. The issue to be examined in particular is the Eklek dance as the foundation within the scope of non-formal education and training courses at Pradapa Loka Bhakti. The issues are as follow: (1) What causes Pradapa Loka Bhakti to use the Eklek dance as the foundation of its basic learning material?, (2) What are the forms within the performing of Eklek dance, and what is the process of the students at Pradhapa Loka Bhakti? (3) Why do the dance forms of the students of Pradhapa Loka Bhakti give a particular aesthetic experience?. In reviewing the experience of dance education, concepts were used from (1) Desmond Morris, concerning elements of preservation and regeneration. (2) Margaret N.H. Doubler, used to analyze the aesthetic experience of the students, (3) David A Kolb, used to analyze the process of the learning style of the students. To illustrate these aspects, this study uses the approach of ethnochoreography combined with with history, sociology and aesthetics. This research apllies dance tenography method by Getrude Prokosch Kurath’s model, data was collected with the following techniques: observation, description, and recordings (visual/audio visual); laboratory study; explanations of style/appearance with cross checks on resources and in-depth interviews when laboratory studies were unstatisfactory; and finally presenting results in a format compliant with the original purpose. The study results show that the Eklek dance posesses a learning style which is divergent and covergent; and assimilated from the experience of the students’ feelings, thoughts, observations, and actions. The peculiarties of the dance are apparent in the tanjak position, the trecet side motion patterns, the oglengan movements, the entragan, and the berikan movements. The formation of the position pattern adeg was created using traditonal methods which have been preserved until the present, in an effort to realize preservation and regeneration are still firmly in place.